Methanogenic Activity and Microbial Community Structure in Response to Different Mineralization Pathways of Ferrihydrite in Paddy Soil - Zhuang, Li; Tang, Ziyang; Yu, Zhen; Li, Jian; Tang, Jia (Frontiers in Earth Science, 2019)
In soils and sediments, microbial reduction of iron (hydr)oxides and consequent formation of secondary iron minerals are important factors influencing many biogeochemical cycles and processes that including microbial methanogenesis. Here, we investigated methanogenic activity and microbial community of a paddy soil enrichment in response to different biomineralization pathways of ferrihydrite, which was reduced and transformed to magnetite and vivianite in the absence and presence of phosphate, respectively. For methanogenic degradation of both acetate and propionate, CH4 production rates in the magnetite-cultures were significantly enhanced compared with the vivianite-cultures. Characterization of 16S rRNA genes from methanogenic soils microbial community indicated that: (i) Methanocellaceae and Methanosarcinaceae were the dominant methanogens in all soil enrichments, (ii) syntrophic acetate-oxidizing bacteria of Clostridiaceae and syntrophic propionate-oxidizing bacteria of Syntrophobacteraceae were highly enriched in the magnetite-cultures, and (iii) the abundance of Anaerolineaceae was increased in the magnetite-cultures for both acetate- and propionate-fed incubations. The facilitated CH4 production in the magnetite-cultures might be related to the dynamic cycle of Fe(III)−Fe(II)−Fe(III) or magnetite-stimulated direct interspecies electron transfer between syntrophic acetate/propionate oxidizers and methanogens, which need further investigation. These results lend insight into the biogeochemical cycling of Fe, C and P in anaerobic soils and sediments, as well as the development of mitigation strategies of CH4 production.